2012
DOI: 10.1096/fj.12-206862
|View full text |Cite
|
Sign up to set email alerts
|

CD36 level and trafficking are determinants of lipolysis in adipocytes

Abstract: CD36 has been linked to the etiology of insulin resistance and inflammation. We explored its function in regulating adipose tissue lipolysis, which influences fat accumulation by liver and muscle and overall metabolism. Knockdown of CD36 in differentiated 3T3-L1 adipocytes decreased lipolysis in response to 10 μM of the β-adrenergic agonist isoproterenol (by 42%), 10 μM of the adenyl cyclase activator forskolin (by 32%), and 500 μM of the phosphodiesterase (PDE) inhibitor isobutylmethylxanthine (by 33%). All t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 47 publications
4
53
1
Order By: Relevance
“…Furthermore, subcutaneous and gonadal adipose tissue mass in CD36-null mice is significantly lower as compared to wild-type littermates [17]. However, in vitro studies showed that the TAG accumulation was significantly increased (about 1.7-fold) by CD36 knock-down in 3T3-L1 adipocytes [41]. This discrepancy was previously attributed to the different sources of TAG accumulation.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, subcutaneous and gonadal adipose tissue mass in CD36-null mice is significantly lower as compared to wild-type littermates [17]. However, in vitro studies showed that the TAG accumulation was significantly increased (about 1.7-fold) by CD36 knock-down in 3T3-L1 adipocytes [41]. This discrepancy was previously attributed to the different sources of TAG accumulation.…”
Section: Discussionmentioning
confidence: 90%
“…FAT/CD36 level and trafficking are determinants of lipolysis in adipocytes. 59 It is strictly located in adipocyte lipid rafts and is translocated to the membrane by insulin, 60 where it mediates long fatty acid chain uptake, including oleic acid 61 and 65% of oxidized lipids uptake and degradation. 57 Activation of FAT/CD36 stimulates the proinflammatory response of adipocytes, possibly through activation of mitochondrial fatty-acid oxidation which increases during differentiation, 62,63 induction of endoplasmic stress 53 and in turn activates JNK to impair insulin signaling in adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…For the FFA measurement, lipids from culture media were extracted in the presence of an internal control (C19:0 FA), and separated on silica gel 60 Å plates as previously described ( 13 ). The FFA fraction was scrapped from the TLC plates and collected in glass tubes after visualization with 0.01% rhodamine 6G.…”
Section: Measurement Of Glycerol Ffa and Prostaglandinsmentioning
confidence: 99%
“…The 3T3-L1 cells (from American Type Culture Collection) were cultured to confl uence in DMEM with 4.5 mg/ml glucose containing 20% calf serum, as described previously ( 13 ). Two days after confl uence, differentiation was initiated by incubation with DMEM containing 10% FBS, 500 µM isobutylmethylxanthine (IBMX), 0.25 µM dexamethasone, and 4 µg/ml insulin for 2 days.…”
Section: Cell Culturementioning
confidence: 99%